Bioactivity Assessment of 8-Hydroxyquinoline and Monosodium Glutamate Mixed Ligand Copper Complex: Experimental and Computational - Bamigboye, Mercy; Ayuba Mustapha,; Friday Danjuma, (University of Thi-Qar Journal of Science, 2024)
The search for substances with biological activity is a prime responsibility of researchers. Coordination compounds with pharmacological activity have been essential and indispensable, especially to humans, especially organic-inorganic hybrid complexes. 8-hydroxyquinoline and Monosodium glutamate ligands were used to synthesize the copper complex by simple one-pot mixing at 35 °C. This formed complex was analysed by microanalytical, spectral, thermal, and computational techniques to characterize its formula and structure. Antimicrobial and In-silico activity was also determined. FT-IR spectroscopy revealed that the complex coordinated through the O-H and N-pyridine ring of Hydroxyquinoline/hydroxyl of the glutamic, confirming the suggestion of the bidentate nature of each coordinating ligand via ON/O ends. Square-planar geometry was posited for Cu, and its decomposition was observed to have decomposed around 471 °C. The proposed structure of the complex was optimised using DFT calculations, and In-silico was assessed. Target prediction, molecular docking, and ADME programs were used to evaluate the biological activity of the complex towards receptors in homo sapiens specie. In all assessments, docking scores indicated a high activity of the Cu complex as the maximum spontaneity was observed in the binding energy for the complex as an antimicrobial agent. In-vitro antimicrobial study for the complexes against six species: Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi and Clostridium botulinum, with maximum bactericidal effect observed in Cu complex against at 22 ± 2.72 mm at 250mg/mL profiling dosage demonstrating its potential as a pharmacological agent.